2021
DOI: 10.21776/ub.ruas.2021.019.02.10
|View full text |Cite
|
Sign up to set email alerts
|

Perbedaan Kegiatan Penghuni di Ruang Makan dengan Ruangan lain berdasarkan ketersediaan Ruang Makan pada Hunian

Abstract: The existence of a dining room is now rarely found in some residences. Some people who do not have a dining room will be forced to use a room to carry out eating activities. In comparison, other people use the dining room to do other activities. It shows that the existence of space reflects the behaviour of the occupants in living. This study will compare community activities with residential conditions with a dining room and those without a dining room. This study aims to reveal the differences and activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…A study on eating behavior in Indonesia stated that very few houses have dedicated dining tables and chairs, regardless of the socioeconomic status (Roshita et al, 2021). According to Putri et al (2021), the increasingly rare presence of a dining room in Indonesian dwellings has forced the occupants to do their dining activities in other rooms in the dwelling. Meanwhile, Putra, Ju, and Soedarsono (2016) found that the dining rooms tend to be passive and rarely used for dining activities even when they are available in a dwelling.…”
Section: Literature Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A study on eating behavior in Indonesia stated that very few houses have dedicated dining tables and chairs, regardless of the socioeconomic status (Roshita et al, 2021). According to Putri et al (2021), the increasingly rare presence of a dining room in Indonesian dwellings has forced the occupants to do their dining activities in other rooms in the dwelling. Meanwhile, Putra, Ju, and Soedarsono (2016) found that the dining rooms tend to be passive and rarely used for dining activities even when they are available in a dwelling.…”
Section: Literature Studymentioning
confidence: 99%
“…The dining room discussed in this section is a formal dining room defined through the affordance attributes, namely the dining table and chairs (Jones, 2018). Putri et al (2021) found that the dining rooms are not only used for dining but also afford various other hidden activities. Although similar findings were found in this research, this section focuses on the dining room for its function according to the determinism approach, which is to afford dining activities, providing a qualitative explanation of the supporting affordance attributes.…”
Section: The Dining Room As Dining Settingmentioning
confidence: 99%